Pengaruh Budaya Organisasi, Lingkungan Kerja dan Gaya Kepemimpinan, Terhadap Kinerja Pegawai di Badan Usaha Pelabuhan Laut BP Batam - Septyadi, Rosemy; Auzar, Silvia Revana (Universitas Batam, 2022)
The Port Business Entity is one of the port management business units in Batam which is special because it is not managed directly by the Directorate General of Sea Transportation, but is managed by the Batam Free Trade Area and Free Port Concession Agency. The output of BUP is port services. anchoring service activities in the form of dock mooring services, water services, loading and unloading services, rental services for stacking/warehouse areas, scout and tug services, and finally through put services (especially at the Kabil liquid bulk port). As one of the business units managed by the Batam Free Trade Area and Free Port Concession Board, employees are required to report all activities carried out to the Batam Free Trade and Free Port Concession Board. Before the activity report is submitted to the Batam Free Trade Area and Free Port Concession Board, the personnel section is obliged to control its employees for the success of the realization of work targets such as the provision and service of port services. The purpose of this study was to determine the influence of organizational culture, work environment and leadership style on the performance of Batam Port Business Entity Office employees, either partially or simultaneously. The research method used is quantitative and qualitative methods based on primary in the form of questionnaires and secondary data from agencies. The number of samples in this study were 104 respondents who were employees of the Batam Port business entity office. The data analysis technique was carried out by multiple linear regression analysis with the help of SPSS statistical tools. The results of the study found that organizational culture had a significant partial effect on employee performance. The work environment has no significant effect partially on employee performance. Leadership style partially significant effect on employee performance. Organizational culture, work environment and leadership style simultaneously have a significant effect on performance.